O “Ciclo de estudos selvagem” e a comunicação decolonial - Oliveira, Cássia (2023)
The aim of this research is to investigate and analyze the documents, educational actions and information and communication objects of the Ciclo de estudos Selvagem (Wild Study Cycle), highlighting how this knowledge is disseminated, in order to highlight its decolonial character. Selvagem is a free course of studies on life that articulates indigenous, traditional, academic, and scientific knowledge by offering a series of actions and materials in different formats free of charge: notebooks, arrows (videos), lectures, books, library, living schools and other actions. It is a production of knowledge that addresses issues related to the areas of environment, ecology, art, history, botany, stories of origin of the world, natural medicine, among others. The problem question that guides the research is: how does the Ciclo de Estudos Selvagem rethink traditional modes of communicational exercise and relate to a decolonial communication? Our hypothesis is that the Ciclo de Estudos Selvagem is configured as a collective communication environment, marked by the experience of bonding, which prioritizes and values the diversity of knowledge working for its articulation, reconfiguring both the dynamics of knowledge production and communicational action from specific informational practices. The theoretical framework of the research is based on the key concepts of communication, information, indigenous information, informational practices, decoloniality and decolonial communication. From a methodological point of view, the qualitative research foresees the use of netnography with the use of exploratory analysis of project documents (reports, notebooks, arrows, available conversations etc.), observation and the analysis of some informational practices based on categories highlighted by a specific model of informational practices. From this conceptual and methodological framework, we seek to understand the dynamics of content production to identify decolonial practices in their knowledge production process. We assume that the Ciclo de Estudos Selvagem acts in favor of the decentralization of knowledge, through a community marked by diversity and a dynamic of knowledge production based on human plurality, articulating different mechanisms of research and knowledge. We believe that this experience is linked to decolonial thinking, consolidating itself as a communicational exercise that rethinks the monocultural logic of knowledge and information in its field.